The Initial Oral Microbiota of Neonates Among Subjects With Gestational Diabetes Mellitus - He, Zhijiang; Wu, Jiaman; Xiao, Bin; Xiao, Shanqiu; Li, Hongping; Wu, Kaifeng (Frontiers in Pediatrics, 2019)
Objective: The objective was to investigate the potential effect of gestational diabetes mellitus on the initial neonatal oral microbiome community structure. Methods: Oral samples were collected from 20 full-term, vaginally delivered newborns with sterile swabs. 9 of them had mothers diagnosed with gestational diabetes mellitus (GDM group), while 11 had non-diabetic mothers (NDM group). The oral microbiota was analyzed using multi-barcode 16S rRNA sequencing on Illumina MiSeq system. Results: The results showed that the birth weight, gestational age and gestational weight gain were significantly higher in NDM group. There was a significant correlation between gestational age and birth weight. Neonatal oral microbiome was composed of five dominant phyla from Actinobacteria, Bacteroidetes, Firmicutes, Proteobacteria and Tenericutes. Compared to NDM group, a higher alpha diversity and reduction of phylum Firmicutes were observed in GDM group. Genus Lactobacillus dominated in NDM group, while Alistipes, Streptococcus and Faecalibacterium were overabundant in GDM group. Additionally, carbohydrate metabolism increased in NDM group, whereas amino acid metabolism, vitamin metabolism and lipopolysaccharide biosynthesis were more abundant in GDM group. Conclusions: This study showed a distinct oral microbiota profile in neonates born to mothers with GDM, which indicated that maternal diabetes status played an important role in neonatal initial oral microbiota.